2016
DOI: 10.1007/s11524-016-0029-x
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Contribute to Intimate Partner Violence Against Women in Urban, Conflict-Affected Settings? Qualitative Findings from Abidjan, Côte d’Ivoire

Abstract: Rapid urbanization is a key driver of the unique set of health risks facing urban populations. One of the most critical health hazards facing urban women is intimate partner violence (IPV). In post-conflict urban areas, women may face an even greater risk of IPV. Yet, few studies have examined the IPV experiences of urbandwelling, conflict-affected women, including those who have been internally displaced. This study qualitatively examined the social and structural characteristics of the urban environment that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 31 publications
0
77
0
Order By: Relevance
“…The current findings echo the qualitative masculinities literature that suggests men's inability to meet the expectations of being a provider may result in their use of violence. 10 The other important pathway proposed in this study's conceptual framework and confirmed in the SEM was relationship quality. Quarreling has long been seen as a trigger for women's experience of IPV, 29 but only one study has found quarreling to be related to men's use of IPV.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The current findings echo the qualitative masculinities literature that suggests men's inability to meet the expectations of being a provider may result in their use of violence. 10 The other important pathway proposed in this study's conceptual framework and confirmed in the SEM was relationship quality. Quarreling has long been seen as a trigger for women's experience of IPV, 29 but only one study has found quarreling to be related to men's use of IPV.…”
Section: Discussionmentioning
confidence: 60%
“…9 In qualitative research in Cote d'Ivoire, the stress of food insecurity and urban poverty led to IPV perpetration among men, who felt unable to meet their gendered role of providing for the family. 10 No other research, to the authors' knowledge, has assessed the relationship between food insecurity and men's IPV perpetration.…”
mentioning
confidence: 99%
“…In countries like northern Uganda, Ethiopia, and DRC, over two decades of conflict and gender-based violations have served to reinforce a culture of disregard, and thus impunity, for diverse forms of violence [24][25][26]. Prolonged displacement brings about community apathy, because social cohesion and trust are eroded by war [27]; additionally, domestic violence becomes normalized, families live in chaotic, overcrowded settlements without any form of privacy. In other words, private incidents of violence become known to neighbors and, being a frequent occurrence, the community becomes numb.…”
Section: Violencementioning
confidence: 99%
“…In northern Uganda, Stark et al [25] explored violence among 204 households and identified that about 50% of respondents had experienced intimate partner violence in their marriages. Cardoso et al's work expanded on the causes of marital rape, associating its prevalence with social and structural changes to the environment of the displaced [27]. The study, conducted in Cote d'Ivoire in West Africa, identifies that urban poverty-with its high male unemployment, food insecurity, financial stress, and cramped housing-played a role in women's experiences with intimate partner violence.…”
Section: Violencementioning
confidence: 99%
See 1 more Smart Citation